Key Developments in IMF Policy Work : October 12, 2008-April 22, 2009. (Policy Papers; Policy Paper, 2009)
This paper summarizes key developments in the Fund's policy work since the 2008 Annual Meetings. Table 1 presents key conclusions of policy initiatives. Table 2 provides a progress report on implementation of the Fund's surveillance priorities.